Innovation, institutions and economic growth in sub-Saharan Africa – an IV estimation of a panel threshold model - Forson, Joseph Ato; Opoku, Rosemary Afrakomah; Appiah, Michael Owusu; Kyeremeh, Evans; Ahmed, Ibrahim Anyass; Addo-Quaye, Ronald; Peng, Zhen; Acheampong, Ernest Yeboah; Bingab, Bernard Bekuni Boawei; Bosomtwe, Emmanuel; Awoonor, Akorkor Kehinde (Journal of Economic and Administrative Sciences, 2021)
PurposeThe significant impact of innovation in stimulating economic growth cannot be overemphasized, more importantly from policy perspective. For this reason, the relationship between innovation and economic growth in developing economies such as the ones in Africa has remained topical. Yet, innovation as a concept is multi-dimensional and cannot be measured by just one single variable. With hindsight of the traditional measures of innovation in literature, we augment it with the number of scientific journals published in the region to enrich this discourse.Design/methodology/approachWe focus on an approach that explores innovation policy qualitatively from various policy documents of selected countries in the region from three policy perspectives (i.e. institutional framework, financing and diffusion and interaction). We further investigate whether innovation as perceived differently is important for economic growth in 25 economies in sub-Saharan Africa over the period 1990–2016. Instrumental variable estimation of a threshold regression is used to capture the contributions of innovation as a multi-dimensional concept on economic growth, while dealing with endogeneity between the regressors and error term.FindingsThe results from both traditional panel regressions and IV panel threshold regressions show a positive relationship between innovation and economic growth, although the impact seems negligible. Institutional quality dampens innovation among low-regime economies, and the relation is persistent regardless of when the focus is on aggregate or decomposed institutional factors. The impact of innovation on economic growth in most regressions is robust to different dimensions of innovation. Yet, the coefficients of the innovation variables in the two regimes are quite dissimilar. While most countries in the region have offered financial support in the form of budgetary allocations to strengthen institutions, barriers to the design and implementation of innovation policies may be responsible for the sluggish contribution of innovation to the growth pattern of the region.Originality/valueSegregating economies of Africa into two distinct regimes based on a threshold of investment in education as a share of GDP in order to understand the relationship between innovation and economic growth is quite novel. This lends credence to the fact that innovation as a multifaceted concept does not take place by chance – it is carefully planned. We have enriched the discourse of innovation and thus helped in deepening understanding on this contentious subject.